2019
DOI: 10.1021/acs.jpclett.9b00560
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Probabilities for Highly Activated Reaction of Polyatomic Molecules on Surfaces Using a High-Dimensional Neural Network Potential: CHD3 + Cu(111)

Abstract: An accurate description of reactive scattering of molecules on metal surfaces often requires the modeling of energy transfer between the molecule and the surface phonons. Although ab initio molecular dynamics (AIMD) can describe this energy transfer, AIMD is at present untractable for reactions with reaction probabilities smaller than 1%. Here, we show that it is possible to use a neural network potential to describe a polyatomic molecule reacting on a mobile metal surface with considerably reduced computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 68 publications
(142 reference statements)
6
89
0
Order By: Relevance
“…Another important dynamical aspect of the reaction of methane is the energy transfer from the molecule to the surface. 54 Figure 6 compares for scattered trajectories this energy transfer from CHD 3 to Cu(111), 54 Pt(111), 65 Ni(111), 12 and Pd(111), where the energy transfer E T is defined aswhere V and K are the potential free and kinetic energy of methane at the initial (i) and final (f) steps of the scattered trajectories, respectively. In general, it is observed that the lower the surface atom mass is, the higher the energy transfer is from methane to the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important dynamical aspect of the reaction of methane is the energy transfer from the molecule to the surface. 54 Figure 6 compares for scattered trajectories this energy transfer from CHD 3 to Cu(111), 54 Pt(111), 65 Ni(111), 12 and Pd(111), where the energy transfer E T is defined aswhere V and K are the potential free and kinetic energy of methane at the initial (i) and final (f) steps of the scattered trajectories, respectively. In general, it is observed that the lower the surface atom mass is, the higher the energy transfer is from methane to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Energy transfer from methane to Ni(111) (blue squares), Pd(111) (black circles), Pt(111) 65 (red triangles), and Cu(111) 54 (green diamonds) compared to the refined Baule model. The solid lines without symbols indicate results predicted by the refined Baule model, whereas the dashed and dotted lines with solid and open symbols indicate laser-off and ν 1 = 1 results, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We still discuss the valuable experimental results on associative desorption since they do provide insight into the reaction dynamics. However, as we will discuss, it is fraught with difficulty to make a direct quantitative comparison between calculations on dissociative chemisorption and associative desorption experiments without improving our dynamical model by incorporating phonons and ehp excitations, which is challenging to do [148][149][150] . Recently, this has been done for H 2 + Cu(111) 75 using ab initio molecular dynamics with electronic friction (AIMDEF) calculations employing the PBE 115 DF.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, multiple symmetry functions of each type are used in the descriptor, each with a different parametrization (ζ, λ, η, R s and κ), encoding different portions of the chemical envi-ronment. While no optimal parameter set exists, the choice of parameters is guided by the generally desired properties of a descriptor previously listed (unique, continuous and compact), and various alternatives for different applications can be found in the literature [51][52][53].…”
Section: Atom-centered Symmetry Functionsmentioning
confidence: 99%